Effectiveness of the corrective and preventive action program made by Oleochemicals (M) Sdn Bhd towards customer complaint under company product / Nor Hashimah Omar - Omar, Nor Hashimah (Faculty of Business and Management, 2005)
It is important for the industrial marketer to understand and effectively manage the process of complaining behavior in which dissatisfied buyers typically engage. By better managing this process, marketers can improve customer loyalty and prevent buyers from undertaking further complaining behavior, which may damage the seller's reputation. Reports on the types of order problems that occur with suppliers, as well as buyers' perceptions of the effectiveness of supplier responses to different types of complaints from the buyer.